International University student helping out in gotong-royong at Madrasah Daniyah Durrulilmi - UMP, PNC (Pejabat Naib Canselor, 2016)
Universiti Malaysia Pahang (UMP) international students took part in a gotongroyong to spruce up Madrasah Daniyah Durrulilmi at Kampung Padang Jaya, Jaya Gading Kuantan on January 17, 2016.